Nanomaterials-Technology of Cadmium Sulphide Nanowire Production by Crystalline Sodium Sulphide Nonahydrate - BOROWSKI, TOMASZ (Asian Journal of Chemistry, 2010)
The developed method allows receiving cadmium sulphide nanowires safely, cheaply and simply. In this method, sodium sulphide nonahydrate as a solid compound was used. By-products, in the form of toxic gas (hydrogen sulphide), occur in small quantities. The length of cadmium sulphide nanowires averages 60 mm, whereas their diameter is 200 nm on average.